Performance Analysis of (Bi2Te3-PbTe) Hybrid Thermoelectric Generator - Anitha Angeline A; Jayakumar J; Lazarus Godson Asirvatham (Institute of Advanced Engineering and Science, 2017)
A theoretical analysis on the performance of (Bi2Te3-PbTe) hybrid thermoelectric generator (TEG) is presented in this paper. The effect of different performance parameters such as output voltage, output current, output power, maximum power output, open circuit voltage, Seebeck co-efficient, electrical resistance, thermal conductance, figure of merit, efficiency, heat absorbed and heat removed based on maximum conversion and power efficiency have been analyzed by varying the hot side temperature up to 350oC and by varying the cold side temperature from 30oC to 150oC. The results showed that a maximum power output of 21.7 W has been obtained with the use of one hybrid thermoelectric module for a temperature difference of 320oC between the hot and cold side of the thermoelectric generator at matched load resistance. The figure of merit was found to be around 1.28 which makes its usage possible in the intermediate temperature (250oC to 350oC) applications such as heating of Biomass waste, heat from Biomass cook stoves or waste heat recovery etc. It is also observed that the hybrid thermoelectric generator offers superior performance over 250oC of the hot side temperature, compared to standard Bi2Te3 modules